Flame-retardant polyurethane ABS (Acrylonitrile Butadiene Styrene) material and preparation method thereof
By adding modified polyurethane and reinforced fillers to ABS materials, a blending system with covalent bonding is formed, which solves the problem of insufficient performance of ABS materials in weather resistance, flame retardant and mechanical aspects, and maintains thermal conductivity and meets market demand. .
Patent Information
- Application Number
- CN202411872290.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing ABS materials have insufficient performance in weather resistance, flame retardant and mechanical aspects, and the thermal conductivity cannot meet market demand.
By adding modified polyurethane and reinforced filler to blend with ABS material, a covalent bonded blending system is formed to improve the mechanical properties, and the flame retardant performance is improved through the combination of silicon-nitrogen-phosphorus flame retardant system and hydroxy iron oxide.
It has achieved significant improvements in weather resistance, flame retardant and mechanics of ABS materials, while maintaining good thermal conductivity and meeting market demand.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ABS materials, and in particular to a flame-retardant polyurethane ABS material and a preparation method thereof. Background Art
[0002] ABS resin is a widely used general-purpose engineering thermoplastic, widely used in home appliances and electronic and electrical industries. As electronic products develop towards being lighter, thinner and smaller, higher requirements are placed on the thermal conductivity of the ABS materials used. At the same time, since the butadiene in ABS still has a double bond structure after polymerization, ABS itself also has defects such as poor weathering and discoloration resistance and flammability. In addition, ABS itself has relatively low heat resistance and insufficient mechanical properties, and has gradually been unable to meet market demand. Summary of the invention
[0003] The purpose of the present invention is to provide a flame-retardant polyurethane ABS material and a preparation method thereof. By adding modified polyurethane and reinforcing filler to blend with the ABS material, the problem of insufficient performance of the existing ABS material in terms of weather resistance, flame retardancy and mechanics is solved, while it can still maintain good thermal conductivity to meet the requirements.
[0004] The object of the present invention can be achieved by the following technical scheme: A method for preparing a flame-retardant polyurethane ABS material, comprising the following steps: Step S1: weighing the following raw materials in parts by weight: 60-70 parts of ABS resin, 15-18 parts of modified polyurethane, 6-8 parts of reinforcing filler, 0.8-1 part of antioxidant and 0.5-0.8 part of lubricant; Step S2: adding ABS resin, modified polyurethane, reinforcing filler, antioxidant and lubricant into a plasticator, plasticizing, drawing, vulcanizing, and obtaining a flame-retardant polyurethane ABS material; The modified polyurethane is prepared by the following steps: Step A1: octaaminopropyl caged polysilsesquioxane and methanol are mixed, and vanillin is added under stirring at a rate of 300-400 rpm and room temperature, and the mixture is reacted for 24 hours to obtain intermediate 1; intermediate 1, sodium hydroxide and deionized water are mixed, and 3-chloro-1,2-propanediol is added under stirring at a rate of 120-140 rpm and a temperature of 80° C., and the mixture is reacted for 4-6 hours to obtain intermediate 2; The dosage ratio of octaaminopropyl caged polysilsesquioxane, methanol and vanillin is 0.01-0.012 mol: 120-140 mL: 0.08-0.09 mol; the dosage ratio of intermediate 1, sodium hydroxide, deionized water and 3-chloro-1,2-propylene glycol is 0.01-0.012 mol: 8-9 g: 100-120 mL: 0.08-0.085 mol; During the reaction, the amino group in the octaaminopropyl caged polysilsesquioxane reacts with the aldehyde group in vanillin to form an imine structure to obtain intermediate 1. Then, under alkaline conditions, the hydroxyl group in intermediate 1 reacts with 3-chloro-1,2-propanediol to undergo a nucleophilic substitution reaction to introduce a 1,2-propanediol structure to obtain intermediate 2. Step A2: Intermediate 2, DOPO and N,N-dimethylformamide are mixed, and the mixture is reacted for 10-12 hours at a stirring rate of 150-180 rpm and a temperature of 100° C. to obtain intermediate 3; intermediate 3 is mixed with dimethyl carbonate, and anhydrous potassium carbonate is added under nitrogen protection at a stirring rate of 150-180 rpm and a temperature of 85° C., and the mixture is stirred for 4-5 hours to obtain intermediate 4; The usage ratio of intermediate 2, DOPO and N,N-dimethylformamide is 0.01-0.012 mol: 0.08-0.085 mol: 150-180 mL; the usage ratio of intermediate 3, dimethyl carbonate and anhydrous potassium carbonate is 0.01-0.012 mol: 0.09-0.094 mol: 0.08-0.1 g; During the reaction, the imine structure in intermediate 2 reacts with DOPO to obtain intermediate 3, and the 1,2-propylene glycol structure in intermediate 3 undergoes an ester exchange reaction with dimethyl carbonate to form a cyclic carbonate structure to obtain intermediate 4; Step A3: Mix hydroxymethyldioxolane, thioctic acid and dichloromethane, stir at a rate of 120-140 rpm, add dicyclohexylcarbodiimide and 4-dimethylaminopyridine, and react for 24 hours to obtain intermediate 5; mix intermediate 4, tris(2-aminoethyl)amine and polyethylene glycol, and react for 12 hours at a rate of 80-120 rpm and a temperature of 60° C., then add intermediate 5, and continue to react for 3-4 hours to obtain modified polyurethane; The dosage ratio of hydroxymethyldioxolane, thioctic acid, dichloromethane, dicyclohexylcarbodiimide and 4-dimethylaminopyridine is 0.01-0.012 mol: 0.01-0.012 mol: 40-60 mL: 0.7-0.8 g: 0.5-0.6 g; the dosage ratio of intermediate 4, tris(2-aminoethyl)amine, polyethylene glycol and intermediate 5 is 0.01-0.012 mol: 0.1-0.11 mol: 8-10 g: 0.008-0.01 mol; During the reaction, under the action of dicyclohexylcarbodiimide and 4-dimethylaminopyridine, the hydroxyl group in hydroxymethyldioxolane reacts with the carboxyl group in lipoic acid to form an ester group, and a cyclic carbonate structure is introduced to obtain intermediate 5. The cyclic carbonate in intermediate 4 reacts with the primary amine group in tris(2-aminoethyl)amine to form a carbamate structure, which then reacts with the hydroxyl group in polyethylene glycol to extend the chain, and finally reacts with the cyclic carbonate structure in intermediate 5 to cap the end, thereby obtaining a modified polyurethane. The reinforcing filler is prepared by the following steps: Step B1: Boron nitride, urea and deionized water were mixed and added to a ball mill, and ball milled for 8-10 hours at a rotation speed of 800 rpm and room temperature, washed, and added to a mixed system of carboxyl carbon nanotubes and deionized water, ultrasonically dispersed for 20 minutes, and sodium carbonate solution was added to adjust the pH value to 8, and the temperature was raised to 40°C and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide were added, and the reaction was carried out for 4-6 hours to obtain a precursor 1; The mass fraction of the sodium carbonate solution is 10%, and the amount ratio of the boron nitride crystal, urea, carboxyl carbon nanotubes, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide is 0.4-0.5g: 15-20g: 0.4-0.5g: 0.002mol: 0.002mol; During the reaction, urea is embedded in the boron nitride layer and peeled off during the ball milling process to form a lamellar structure. At the same time, urea is decomposed into free amino groups and grafted onto the boron nitride nanosheets. The urea then undergoes an amidation reaction with the carboxyl carbon nanotubes under the action of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide to obtain precursor 1. Step B2: Precursor 1, ferric chloride hexahydrate and deionized water are mixed, and the mixture is reacted for 12 hours at a stirring rate of 80-100 rpm and a temperature of 120° C. to obtain precursor 2. Precursor 2, ethanol and glacial acetic acid are mixed and ultrasonically dispersed for 15 minutes. 3-(isobutyleneoxy)propyltrimethoxysilane and deionized water are added under stirring at a stirring rate of 80-100 rpm and a temperature of 80° C., and the mixture is reacted for 14-16 hours to obtain a reinforcing filler. The ratio of precursor 1 to ferric chloride hexahydrate is 1.2-1.5 g: 4-6 g; the ratio of precursor 2, glacial acetic acid and 3-(isobutylene acyloxy)propyltrimethoxysilane is 3-4 g: 12-14 mL: 2.5-3 g; During the reaction, ferric oxyhydroxide is prepared by a solution method using ferric chloride hexahydrate as an iron source. Since carboxyl carbon nanotubes are grafted on the surface of precursor 1, ferric oxyhydroxide grows on the surface of precursor 1 to form a three-dimensional structure to obtain precursor 2. Precursor 2 is then modified by 3-(isobutyleneoxy)propyltrimethoxysilane to introduce double bonds to obtain a reinforcing filler. Beneficial effects of the invention: The invention discloses a flame-retardant polyurethane ABS material and a preparation method thereof. By adding modified polyurethane and reinforcing filler to blend with ABS material, the problem of insufficient performance of existing ABS material in terms of weather resistance, flame retardancy and mechanics is solved, while it can still maintain good thermal conductivity to meet the needs; in the process of plasticizing and melt blending, the lipoic acid structure in the modified polyurethane is ring-opened to form a thiol group and reacts with the double bonds in the ABS material and the reinforcing filler, thereby connecting the ABS material, the reinforcing filler and the modified polyurethane with a covalent bond, avoiding the occurrence of thermodynamic incompatibility between the ABS material and the polyurethane, so that a reinforced filler containing a three-dimensional structure is formed. The modified polyurethane is a blended system with the material and cage-type silsesquioxane as nodes. At the same time, the urethane groups existing in large quantities in the modified polyurethane also have hydrogen bond complexation with the ABS material. Under the synergistic effect of its multiple effects, the mechanical properties of the ABS material are greatly improved, and it reacts with the defect sites in the ABS material to enhance its weather resistance. Since the modified polyurethane itself contains DOPO groups and a large amount of nitrogen and silicon elements, it can form a silicon-nitrogen-phosphorus flame retardant system, and the reinforcing filler contains boron nitride and carboxyl carbon nanotubes, which ensure the thermal conductivity of the ABS material, and its in-situ grown oxyhydroxy iron can also complex with the silicon-nitrogen-phosphorus flame retardant system, thereby reflecting excellent flame retardant properties. DETAILED DESCRIPTION
[0005] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0006] Example 1 A method for preparing a flame-retardant polyurethane ABS material comprises the following steps: Step S1: weigh the following raw materials in parts by weight: 60 parts of commercially available PA-749 ABS resin, 15 parts of modified polyurethane, 6 parts of reinforcing filler, 0.8 parts of commercially available 245 antioxidant and 0.5 parts of commercially available pets-ap lubricant; Step S2: adding ABS resin, modified polyurethane, reinforcing filler, antioxidant and lubricant into a plasticator, plasticizing, drawing, vulcanizing, and obtaining a flame-retardant polyurethane ABS material; The modified polyurethane is prepared by the following steps: Step A1: Mix commercially available Qiyue Bio octaaminopropyl caged polysilsesquioxane and methanol, stir and add vanillin at a stirring rate of 300 rpm and room temperature, and react for 24 hours to obtain intermediate 1; mix intermediate 1, sodium hydroxide and deionized water, stir and add 3-chloro-1,2-propanediol at a stirring rate of 120 rpm and a temperature of 80°C, and react for 4 hours to obtain intermediate 2; The ratio of octaaminopropyl caged polysilsesquioxane, methanol and vanillin is 0.01 mol: 120 mL: 0.08 mol; the ratio of intermediate 1, sodium hydroxide, deionized water and 3-chloro-1,2-propylene glycol is 0.01 mol: 8 g: 100 mL: 0.08 mol; Step A2: Intermediate 2, DOPO and N,N-dimethylformamide were mixed, and the mixture was reacted for 10 hours at a stirring rate of 150 rpm and a temperature of 100°C to obtain intermediate 3. Intermediate 3 was mixed with dimethyl carbonate, and anhydrous potassium carbonate was added under nitrogen protection at a stirring rate of 150 rpm and a temperature of 85°C, and the mixture was stirred for 4 hours to obtain intermediate 4. The ratio of intermediate 2, DOPO and N,N-dimethylformamide is 0.01 mol: 0.08 mol: 150 mL; the ratio of intermediate 3, dimethyl carbonate and anhydrous potassium carbonate is 0.01 mol: 0.09 mol: 0.08 g; Step A3: Mix hydroxymethyldioxolane, thioctic acid and dichloromethane, stir at a rate of 120 rpm, add dicyclohexylcarbodiimide and 4-dimethylaminopyridine, and react for 24 hours to obtain intermediate 5; mix intermediate 4, tris(2-aminoethyl)amine and polyethylene glycol, stir at a rate of 80 rpm, and react for 12 hours at 60° C., then add intermediate 5, and continue to react for 3 hours to obtain modified polyurethane; The amount ratio of hydroxymethyldioxolane, thioctic acid, dichloromethane, dicyclohexylcarbodiimide and 4-dimethylaminopyridine is 0.01 mol: 0.01 mol: 40 mL: 0.7 g: 0.5 g; the amount ratio of intermediate 4, tris (2-aminoethyl) amine, polyethylene glycol and intermediate 5 is 0.01 mol: 0.1-0.11 mol: 8 g: 0.008 mol; The reinforcing filler is prepared by the following steps: Step B1: commercially available Borda Technology boron nitride, urea and deionized water were mixed and added to a ball mill, ball milled for 8 hours at a rotation speed of 800 rpm and room temperature, washed, and added to a mixed system of commercially available Clarmar 133415 carboxyl carbon nanotubes and deionized water, ultrasonically dispersed for 20 minutes, sodium carbonate solution was added to adjust the pH value to 8, the temperature was raised to 40°C, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide were added, and the reaction was carried out for 4 hours to obtain precursor 1; The mass fraction of sodium carbonate solution is 10%, and the amount ratio of boron nitride crystal, urea, carboxyl carbon nanotube, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide is 0.4g:15g:0.4g:0.002mol:0.002mol; Step B2: Precursor 1, ferric chloride hexahydrate and deionized water were mixed, and the mixture was reacted for 12 hours at a stirring rate of 80 rpm and a temperature of 120° C. to obtain precursor 2. Precursor 2, ethanol and glacial acetic acid were mixed and ultrasonically dispersed for 15 minutes. 3-(isobutyleneoxy)propyltrimethoxysilane and deionized water were added under stirring at a stirring rate of 80 rpm and a temperature of 80° C., and the mixture was reacted for 14 hours to obtain a reinforcing filler. The usage ratio of precursor 1 and ferric chloride hexahydrate is 1.2g:4g; the usage ratio of precursor 2, glacial acetic acid and 3-(isobutyleneoxy)propyltrimethoxysilane is 3g:12mL:2.5g.
[0007] Example 2 A method for preparing a flame-retardant polyurethane ABS material comprises the following steps: Step S1: Weigh the following raw materials in parts by weight: 70 parts of commercially available PA-749 ABS resin, 15 parts of modified polyurethane, 8 parts of reinforcing filler, 0.8 parts of commercially available 245 antioxidant and 0.8 parts of commercially available pets-ap lubricant; Step S2: adding ABS resin, modified polyurethane, reinforcing filler, antioxidant and lubricant into a plasticator, plasticizing, drawing, vulcanizing, and obtaining a flame-retardant polyurethane ABS material; The modified polyurethane is prepared by the following steps: Step A1: Mix commercially available Qiyue Bio octaaminopropyl caged polysilsesquioxane and methanol, stir and add vanillin at a stirring rate of 400 rpm and room temperature, and react for 24 hours to obtain intermediate 1; mix intermediate 1, sodium hydroxide and deionized water, stir and add 3-chloro-1,2-propanediol at a stirring rate of 120 rpm and a temperature of 80°C, and react for 6 hours to obtain intermediate 2; The amount ratio of octaaminopropyl caged polysilsesquioxane, methanol and vanillin is 0.01 mol: 140 mL: 0.08 mol; the amount ratio of intermediate 1, sodium hydroxide, deionized water and 3-chloro-1,2-propylene glycol is 0.01 mol: 9 g: 100 mL: 0.085 mol; Step A2: Intermediate 2, DOPO and N,N-dimethylformamide were mixed, and the mixture was reacted for 10 hours at a stirring rate of 180 rpm and a temperature of 100°C to obtain intermediate 3. Intermediate 3 was mixed with dimethyl carbonate, and anhydrous potassium carbonate was added under nitrogen protection at a stirring rate of 180 rpm and a temperature of 85°C, and the mixture was stirred for 4 hours to obtain intermediate 4. The ratio of intermediate 2, DOPO and N,N-dimethylformamide is 0.012 mol: 0.085 mol: 150 mL; the ratio of intermediate 3, dimethyl carbonate and anhydrous potassium carbonate is 0.01 mol: 0.094 mol: 0.08 g; Step A3: Mix hydroxymethyldioxolane, thioctic acid and dichloromethane, stir at a rate of 140 rpm, add dicyclohexylcarbodiimide and 4-dimethylaminopyridine, and react for 24 hours to obtain intermediate 5; mix intermediate 4, tris(2-aminoethyl)amine and polyethylene glycol, stir at a rate of 80 rpm, and react for 12 hours at 60° C., then add intermediate 5, and continue to react for 4 hours to obtain modified polyurethane; The amount ratio of hydroxymethyldioxolane, thioctic acid, dichloromethane, dicyclohexylcarbodiimide and 4-dimethylaminopyridine is 0.01 mol: 0.012 mol: 40 mL: 0.8 g: 0.6 g; the amount ratio of intermediate 4, tris (2-aminoethyl) amine, polyethylene glycol and intermediate 5 is 0.01 mol: 0.11 mol: 10 g: 0.008 mol; The reinforcing filler is prepared by the following steps: Step B1: commercially available Borda Technology boron nitride, urea and deionized water were mixed and added to a ball mill, ball milled for 8 hours at a rotation speed of 800 rpm and room temperature, washed, and added to a mixed system of commercially available Clarmar 133415 carboxyl carbon nanotubes and deionized water, ultrasonically dispersed for 20 minutes, sodium carbonate solution was added to adjust the pH value to 8, the temperature was raised to 40°C, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide were added, and the reaction was carried out for 6 hours to obtain precursor 1; The mass fraction of the sodium carbonate solution is 10%, and the amount ratio of boron nitride crystal, urea, carboxyl carbon nanotubes, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide is 0.4g:20g:0.4g:0.002mol:0.002mol; Step B2: Precursor 1, ferric chloride hexahydrate and deionized water were mixed, and the mixture was reacted for 12 hours at a stirring rate of 100 rpm and a temperature of 120° C. to obtain precursor 2. Precursor 2, ethanol and glacial acetic acid were mixed and ultrasonically dispersed for 15 minutes. 3-(isobutyleneoxy)propyltrimethoxysilane and deionized water were added under stirring at a stirring rate of 100 rpm and a temperature of 80° C., and the mixture was reacted for 14 hours to obtain a reinforcing filler. The usage ratio of precursor 1 and ferric chloride hexahydrate is 1.2g:6g; the usage ratio of precursor 2, glacial acetic acid and 3-(isobutyleneoxy)propyltrimethoxysilane is 3g:14mL:2.5g.
[0008] Example 3 A method for preparing a flame-retardant polyurethane ABS material comprises the following steps: Step S1: weigh the following raw materials in parts by weight: 70 parts of commercially available PA-749 ABS resin, 18 parts of modified polyurethane, 8 parts of reinforcing filler, 1 part of commercially available 245 antioxidant and 0.8 parts of commercially available pets-ap lubricant; Step S2: adding ABS resin, modified polyurethane, reinforcing filler, antioxidant and lubricant into a plasticator, plasticizing, drawing, vulcanizing, and obtaining a flame-retardant polyurethane ABS material; The modified polyurethane is prepared by the following steps: Step A1: Mix commercially available Qiyue Bio octaaminopropyl caged polysilsesquioxane and methanol, stir and add vanillin at a stirring rate of 300 rpm and room temperature, and react for 24 hours to obtain intermediate 1; mix intermediate 1, sodium hydroxide and deionized water, stir and add 3-chloro-1,2-propanediol at a stirring rate of 140 rpm and a temperature of 80°C, and react for 4 hours to obtain intermediate 2; The ratio of octaaminopropyl caged polysilsesquioxane, methanol and vanillin is 0.012 mol: 120 mL: 0.09 mol; the ratio of intermediate 1, sodium hydroxide, deionized water and 3-chloro-1,2-propylene glycol is 0.012 mol: 9 g: 120 mL: 0.085 mol; Step A2: Intermediate 2, DOPO and N,N-dimethylformamide were mixed, and the mixture was reacted for 12 hours at a stirring rate of 180 rpm and a temperature of 100°C to obtain intermediate 3. Intermediate 3 was mixed with dimethyl carbonate, and anhydrous potassium carbonate was added under nitrogen protection at a stirring rate of 180 rpm and a temperature of 85°C, and the mixture was stirred for 5 hours to obtain intermediate 4. The ratio of intermediate 2, DOPO and N,N-dimethylformamide is 0.012 mol: 0.085 mol: 180 mL; the ratio of intermediate 3, dimethyl carbonate and anhydrous potassium carbonate is 0.012 mol: 0.094 mol: 0.1 g; Step A3: Mix hydroxymethyldioxolane, thioctic acid and dichloromethane, stir at a rate of 140 rpm, add dicyclohexylcarbodiimide and 4-dimethylaminopyridine, and react for 24 hours to obtain intermediate 5; mix intermediate 4, tris(2-aminoethyl)amine and polyethylene glycol, and react for 12 hours at a rate of 120 rpm and a temperature of 60° C., then add intermediate 5, and continue to react for 4 hours to obtain modified polyurethane; The amount ratio of hydroxymethyldioxolane, thioctic acid, dichloromethane, dicyclohexylcarbodiimide and 4-dimethylaminopyridine is 0.012 mol: 0.012 mol: 60 mL: 0.8 g: 0.6 g; the amount ratio of intermediate 4, tris (2-aminoethyl) amine, polyethylene glycol and intermediate 5 is 0.012 mol: 0.11 mol: 10 g: 0.01 mol; The reinforcing filler is prepared by the following steps: Step B1: commercially available Borda Technology boron nitride, urea and deionized water were mixed and added to a ball mill, ball milled for 10 hours at a rotation speed of 800 rpm and room temperature, washed, and added to a mixed system of commercially available Clarmar 133415 carboxyl carbon nanotubes and deionized water, ultrasonically dispersed for 20 minutes, sodium carbonate solution was added to adjust the pH value to 8, the temperature was raised to 40°C, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide were added, and the reaction was carried out for 6 hours to obtain precursor 1; The mass fraction of the sodium carbonate solution is 10%, and the amount ratio of boron nitride crystal, urea, carboxyl carbon nanotubes, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide is 0.5g:20g:0.5g:0.002mol:0.002mol; Step B2: Precursor 1, ferric chloride hexahydrate and deionized water were mixed, and the mixture was reacted for 12 hours at a stirring rate of 100 rpm and a temperature of 120° C. to obtain precursor 2. Precursor 2, ethanol and glacial acetic acid were mixed and ultrasonically dispersed for 15 minutes. 3-(isobutyleneoxy)propyltrimethoxysilane and deionized water were added under stirring at a stirring rate of 100 rpm and a temperature of 80° C., and the mixture was reacted for 16 hours to obtain a reinforcing filler. The usage ratio of precursor 1 and ferric chloride hexahydrate is 1.5g:6g; the usage ratio of precursor 2, glacial acetic acid and 3-(isobutyleneoxy)propyltrimethoxysilane is 4g:14mL:3g.
[0009] Comparative Example 1 Compared with Example 3, this comparative example replaces octaaminopropyl caged polysilsesquioxane with monoaminopropyl caged polysilsesquioxane in the preparation process of the modified polyurethane, and the other steps are the same.
[0010] Comparative Example 2 Compared with Example 3, this comparative example replaces lipoic acid with octanoic acid in the preparation process of modified polyurethane, and the other steps are the same.
[0011] Comparative Example 3 Compared with Example 3, in this comparative example, the precursor 2 in the preparation process of the reinforcing filler is replaced by the precursor 1 of Example 3, and the other steps are the same.
[0012] Take a flame-retardant polyurethane ABS material prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3, refer to GB / T 1410-2006, make the ABS material into a round piece with a diameter of 80 mm and a thickness of 3 mm, use a thermal constant analyzer to test its thermal conductivity, refer to GB / T 9341-2000, test its bending strength, place the sample in a UV aging box for UV aging, the light source is a UVA-340 fluorescent UV lamp, and the light intensity is 0.76 W·m -2 ·nm -1 , the temperature is 50℃, the aging time is 28d, and then the bending strength is tested, and the performance retention rate is calculated to evaluate its weather resistance. The vertical burning test and limiting oxygen index test are carried out with reference to ASTM D 3801 and GB / T 2406.1-2008. The test results are shown in Table 1: Table 1 Test results Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Thermal conductivity (W / (m·K)) 1.38 1.40 1.41 1.39 1.40 1.35 Bending strength (MPa) 113.8 114.1 114.2 108.1 102.4 98.17 Performance retention rate (%) 98.56 98.67 98.72 98.21 84.76 97.93 Limiting oxygen index (%) 31.11 32.35 32.41 29.47 30.55 28.72 Vertical burning level V-0 V-0 V-0 V-1 V-1 V-2 It can be seen from the test results in the table shown that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1, Comparative Example 2 and Comparative Example 3, Comparative Example 1 replaces the octaaminopropyl caged polysilsesquioxane in the preparation process of the modified polyurethane with a monoaminopropyl caged polysilsesquioxane, and its performance is reduced due to the lack of the DOPO group and the branched structure formed by the octaaminopropyl caged polysilsesquioxane. Comparative Example 2 replaces lipoic acid with octanoic acid in the preparation process of the modified polyurethane, and its performance is reduced due to the lack of covalent bond connection. Comparative Example 3 replaces Precursor 2 in the preparation process of the reinforcing filler with Precursor 1 in Example 3, and its performance is reduced due to the lack of iron oxyhydroxide and a three-dimensional structure.
[0013] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0014] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a flame-retardant polyurethane ABS material, characterized in that: The method comprises the following steps: Step S1: weighing the following raw materials in parts by weight: 60-70 parts of ABS resin, 15-18 parts of modified polyurethane, 6-8 parts of reinforcing filler, 0.8-1 parts of antioxidant and 0.5-0.8 parts of lubricant; Step S2: adding ABS resin, modified polyurethane, reinforcing filler, antioxidant and lubricant into a plasticator, plasticizing, drawing, vulcanizing, and obtaining a flame-retardant polyurethane ABS material.
2. The method for preparing a flame-retardant polyurethane ABS material according to claim 1, characterized in that: The modified polyurethane is prepared by the following steps: Step A1: octaaminopropyl caged polysilsesquioxane and methanol are mixed, and vanillin is added under stirring at a rate of 300-400 rpm and room temperature, and the mixture is reacted for 24 hours to obtain intermediate 1; intermediate 1, sodium hydroxide and deionized water are mixed, and 3-chloro-1,2-propanediol is added under stirring at a rate of 120-140 rpm and a temperature of 80° C., and the mixture is reacted for 4-6 hours to obtain intermediate 2; Step A2: Intermediate 2, DOPO and N,N-dimethylformamide are mixed, and the mixture is reacted for 10-12 hours at a stirring rate of 150-180 rpm and a temperature of 100° C. to obtain intermediate 3; intermediate 3 is mixed with dimethyl carbonate, and anhydrous potassium carbonate is added under nitrogen protection at a stirring rate of 150-180 rpm and a temperature of 85° C., and the mixture is stirred for 4-5 hours to obtain intermediate 4; Step A3: Mix hydroxymethyldioxolane, thioctic acid and dichloromethane, stir at a rate of 120-140 rpm, add dicyclohexylcarbodiimide and 4-dimethylaminopyridine, and react for 24 hours to obtain intermediate 5. Mix intermediate 4, tris(2-aminoethyl)amine and polyethylene glycol, and react for 12 hours at a rate of 80-120 rpm and a temperature of 60°C. Then add intermediate 5 and continue to react for 3-4 hours to obtain modified polyurethane.
3. The method for preparing a flame-retardant polyurethane ABS material according to claim 2, characterized in that: In step A1: the usage ratio of octaaminopropyl caged polysilsesquioxane, methanol and vanillin is 0.01-0.012 mol: 120-140 mL: 0.08-0.09 mol; the usage ratio of intermediate 1, sodium hydroxide, deionized water and 3-chloro-1,2-propylene glycol is 0.01-0.012 mol: 8-9 g: 100-120 mL: 0.08-0.085 mol.
4. The method for preparing a flame-retardant polyurethane ABS material according to claim 2, characterized in that: In step A2: the usage ratio of intermediate 2, DOPO and N,N-dimethylformamide is 0.01-0.012 mol: 0.08-0.085 mol: 150-180 mL; the usage ratio of intermediate 3, dimethyl carbonate and anhydrous potassium carbonate is 0.01-0.012 mol: 0.09-0.094 mol: 0.08-0.1 g.
5. The method for preparing a flame-retardant polyurethane ABS material according to claim 2, characterized in that: In step A3: the amount ratio of hydroxymethyldioxolane, thioctic acid, dichloromethane, dicyclohexylcarbodiimide and 4-dimethylaminopyridine is 0.01-0.012 mol: 0.01-0.012 mol: 40-60 mL: 0.7-0.8 g: 0.5-0.6 g; the amount ratio of intermediate 4, tris (2-aminoethyl) amine, polyethylene glycol and intermediate 5 is 0.01-0.012 mol: 0.1-0.11 mol: 8-10 g: 0.008-0.01 mol.
6. The method for preparing a flame-retardant polyurethane ABS material according to claim 1, characterized in that: The reinforcing filler is prepared by the following steps: Step B1: Boron nitride, urea and deionized water were mixed and added to a ball mill, and ball milled for 8-10 hours at a rotation speed of 800 rpm and room temperature, washed, and added to a mixed system of carboxyl carbon nanotubes and deionized water, ultrasonically dispersed for 20 minutes, and sodium carbonate solution was added to adjust the pH value to 8, and the temperature was raised to 40°C and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide were added, and the reaction was carried out for 4-6 hours to obtain a precursor 1; Step B2: Precursor 1, ferric chloride hexahydrate and deionized water are mixed, and the reaction is carried out for 12 hours at a stirring rate of 80-100 rpm and a temperature of 120°C to obtain precursor 2. Precursor 2, ethanol and glacial acetic acid are mixed and ultrasonically dispersed for 15 minutes. 3-(isobutyleneoxy)propyltrimethoxysilane and deionized water are added under stirring rate of 80-100 rpm and a temperature of 80°C, and the reaction is carried out for 14-16 hours to obtain a reinforcing filler.
7. The method for preparing a flame-retardant polyurethane ABS material according to claim 6, characterized in that: In step B1: the mass fraction of the sodium carbonate solution is 10%, and the amount ratio of the boron nitride crystal, urea, carboxyl carbon nanotubes, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide is 0.4-0.5g: 15-20g: 0.4-0.5g: 0.002mol: 0.002mol.
8. The method for preparing a flame-retardant polyurethane ABS material according to claim 6, characterized in that: In step B2: the ratio of precursor 1 to ferric chloride hexahydrate is 1.2-1.5 g:4-6 g; the ratio of precursor 2, glacial acetic acid and 3-(isobutyleneoxy)propyltrimethoxysilane is 3-4 g:12-14 mL:2.5-3 g.
9. A flame-retardant polyurethane ABS material, characterized in that: Prepared according to any one of the preparation methods described in claims 1-8.
Citation Information
Patent Citations
Fluoride-free flame-retardant PC / ABS composite plastic and preparation method thereof
CN119081340A
Flame retardant ABS and urethane polymers
US3954914A
Pcabs composition, preparation method therefor, and application thereof
WO2022095362A1
Cited By
Low-temperature-resistant PVC / SEBS modified material and preparation method thereof
CN120158012A
Flame-retardant thermoplastic polyester elastomer and preparation method thereof
CN122356734A